Automatic plant waterer / Muhd Muzzammil Sabri and Muhammad Amir Mat Wajer - Sabri, Muhd Muzzammil; Mat Wajer, Muhammad Amir (2002)
The main problem that frequently arises in plant care taking is the aspect o f time that usually people do not have much because they have many more important things to do. This is why some people hire a worker to do this job. But what about those who cannot afford a gardener? Now, there is a gadget that can solve this problem. It is called ‘Automatic Plant Waterer’. This device automatically sprays water to plants whenever they need it. The water sprays within a certain time that is determined by the users. With this, people could save money on gardener and water bills. Furthermore, people do not have to monitor their plant anymore, which will save them a lot o f time.